(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1974)
From six “Crioula” rams (2 to 3.5 years old, weighing 36 to 51 kg), 36 semen collections were made by electric shocks every second day, during 12 days. At the same time, scrotal and body temperatures were taken in each animal. Three of the animals were found to be unilateral cryptorchid and the remaining 3 rams were normal. Analysis of data revealed that concentration and head abnormalities were statistically higher in normal animals. Volume, motility and middle–piece and tails abnormalities levels were still high but not significantly different from those of cryptorchid rams. The differences between scrotal and body temperatures were considered to be normal for the species and did not affect the semen picture.